IbM USAHA TOKO TRADISIONAL DAN UNIT PERTOKOAN KOPERASI DI KABUPATEN JEPARA - Nahar, Aida -; Aminnudin, Moch - (Journal of Dedicators Community, 2022)
The presence of modern stores has led to the climate of unfair competition harmful traditional stores. The existence of a minimarket can turn off 20-50 small grocery stores, while a supermarket can be lethal up to 200 grocery stores, while hypermarkets and 500 grocery stores. minimarket establishment, in a radius of 500 meters will result in a decline in income of up to 57.92 percent. At a radius of 1 km to 30 percent. Defeat competing with traditional stores because of low competitiveness. This situation experienced by both partners, traditional shop "Darul Ulum" and Toko Abdul Khamid.These service activities seek to address the problem of lack of competitiveness in the form of partners, and exacerbated by the low-performance service standards for record-keeping and accounting system is still manual. Therefore, the outcome of devotion is a solution to the problem. Such as 1) program to improve competitiveness, 2) development of accounting information systems. The approach used is a method of interactive participation, in which both partners will play a role in the analysis process for planning activities and the strengthening of internal organization.The method of implementation program to improve competitiveness, carried out in phases: 1) a SWOT Analysis, 2) Guarantee of perception and deal program, 3) Modernization store, 4) Training service standards, 5) Training governance and SOP, 6) creation of SOP shops, 7 ) Implementation and mentoring. Program information systems development shops, stages: 1) analysis of requirements and design of information systems, 2) identification and preparation of database product items and members or prospective members, 3) Making accounting software, 4) Application of accounting information systems, 5) training information system accounting, 6) special units of cooperative stores, to disseminate the members, administrators and managers of cooperatives, 7) Implementation and facilitation of the use of the system. As quality assurance efforts in the implementation of each of the partners will be accompanied by two students.